Engaging the Indigenous Supply Chain during the COVID-19 Pandemic - Carrière-Acco, David (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2022)
This article relates lessons learned about Indigenous supplier engagement during the COVID-19 pandemic. It explores how the Public Services and Procurement Canada (PSPC), Indigenous Services Canada (ISC), and the National Indigenous Organization partnered to form a COVID-19 supplier taskforce to drive PPE and COVID-related service contracting opportunities to Indigenous suppliers to help businesses survive a prolonged economic shutdown. It was successful when both governments and organizations found a way to work together. Challenges included determining ways to support long-term working relationships and agreements, developing required tools and processes, and identifying contracting opportunities. This article describes the journey partners took under the leadership of Cando. Finally, the article concludes with actions taken by the taskforce to ensure that Indigenous suppliers have a place in Canada's economic recovery.